2019
DOI: 10.1016/j.sbi.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches to macromolecular interactions in the cell

Abstract: Structural modeling of a cell is an evolving strategic direction in computational structural biology. It takes advantage of new powerful modeling techniques, deeper understanding of fundamental principles of molecular structure and assembly, and rapid growth of the amount of structural data generated by experimental techniques. Key modeling approaches to principal types of macromolecular assemblies in a cell already exist. The main challenge, along with the further development of these modeling approaches, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…They have focused almost exclusively on validating predictions of the diffusion coefficient of a protein in a crowded cellular environment by measurements of fluorescent proteins diffusion in cells. 10, 22 These results showed that effects like transient interactions and excluded volume significantly decrease the rate of diffusion of proteins in cells. 10…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…They have focused almost exclusively on validating predictions of the diffusion coefficient of a protein in a crowded cellular environment by measurements of fluorescent proteins diffusion in cells. 10, 22 These results showed that effects like transient interactions and excluded volume significantly decrease the rate of diffusion of proteins in cells. 10…”
Section: Introductionmentioning
confidence: 84%
“…10, 22 These results showed that effects like transient interactions and excluded volume significantly decrease the rate of diffusion of proteins in cells. 10…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In recent years molecular simulation techniques have been gaining traction as alternative methods for the elucidation of structural details underpinning cellular mechanisms 1 . Methods like molecular docking can complement experimental techniques such as X-RAY crystallography, NMR and cryo-electron microscopy and allow us to gain insight into the structural machinery of the cell.…”
Section: Introductionmentioning
confidence: 99%